(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the conceptions of 2nd and 3rd year high school students from a public school in Confresa/MT about Physics studies after using PhET simulators. The field research, quantitative and qualitative, of a basic nature, of an exploratory nature, was developed in 2021, which used PhET simulations in Physics classes, and involved high school students from a public school in Confresa/MT. Data collection took place in two moments: initial questionnaire to express how they evaluate the teaching of Physics they had; and another questionnaire, after the application and use of simulations in class, that is, their perceptions about the platform as a facilitator of knowledge, their approaches and possible improvements to the platform. The results were tabulated in graphs and the Content Analysis method was used to analyze the responses. There were two pre-established categories: The importance of PhET simulations for teaching Physics; Perspectives on facilities, difficulties and improvements for the PhET platform. It was found that most students find it difficult to understand or understand equations and relate the contents to everyday aspects. Using the PhET platform, students were able to understand the concepts more clearly and succinctly and observed greater participation in classes. In summary, it is considered that the use of virtual simulations during the educational process is feasible, since each student has their own pace of learning and the different languages used by the simulations facilitate the understanding of the contents.